Adenylate cyclase type 9 antagonizes cAMP accumulation and regulates endothelial signalling involved in atheroprotection. Issue 2 (16th May 2022) - Rautureau, Yohann; Berlatie, Marianne; Rivas, Daniel; Uy, Kurunradeth; Blanchette, Alexandre; Miquel, Géraldine; Higgins, Marie-Ève; Mecteau, Mélanie; Nault, Audrey; Villeneuve, Louis; Lavoie, Véronique; Théberge-Julien, Gabriel; et al.
Abstract: Aims: The adenylate cyclase type 9 ( ADCY9 ) gene appears to determine atherosclerotic outcomes in patients treated with dalcetrapib. In mice, we recently demonstrated that Adcy9 inactivation potentiates endothelial function and inhibits atherogenesis. The objective of this study was to characterize the contribution of ADCY9 to the regulation of endothelial signalling pathways involved in atherosclerosis. Methods and results: We show that ADCY9 is expressed in the endothelium of mouse aorta and femoral arteries. We demonstrate that ADCY9 inactivation in cultured endothelial cells paradoxically increases cAMP accumulation in response to the adenylate cyclase activators forskolin and vasoactive intestinal peptide (VIP). Reciprocally, ADCY9 overexpression decreases cAMP production. Using mouse femoral artery arteriography, we show that Adcy9 inactivation potentiates VIP-induced endothelial-dependent vasodilation. Moreover, Adcy9 inactivation reduces mouse atheroma endothelial permeability in different vascular beds. ADCY9 overexpression reduces forskolin-induced phosphorylation of Ser 157 -vasodilator-stimulated phosphoprotein (VASP) and worsens thrombin-induced fall of RAP1 activity, both leading to increased endothelial permeability. ADCY9 inactivation in thrombin-stimulated human coronary artery endothelial cells results in cAMP accumulation, increases p-Ser 157 -VASP, and inhibits endothelial permeability. MLC2 phosphorylation and actin stress fibre increases in response to thrombin were reduced by ADCY9 inactivation, suggesting actin cytoskeleton regulation. Finally, using the Miles assay, we demonstrate that Adcy9 regulates thrombin-induced endothelial permeability in vivo in normal and atherosclerotic animals. Conclusion: Adcy9 is expressed in endothelial cells and regulates local cAMP and endothelial functions including permeability relevant to atherogenesis. Graphical Abstract: Graphical Abstract